Empowerment: challenges in measurement. (June 2019) - Cross, Ruth; Woodall, James; Warwick-Booth, Louise
Empowerment is core to health promotion; however, there is a lack of consensus in the wider literature as to how to define it and at what level it may occur. Definitional inconsistency inevitably leads to challenges in measuring empowerment; yet if it is as important as is claimed, this must be addressed. This paper discusses the complexities of measuring empowerment and puts forward a number of recommendations for researchers and policy makers as to how this can be achieved noting some of the tensions that may arise between theoretical considerations, research and practice. We argue that empowerment is a culturally and socially defined construct and that this should be taken into account in attempts to measure it. Finally we conclude that, in order to build up the evidence base for empowerment, there is a need for research clearly defining what it is and how it is being measured.